2022
DOI: 10.1352/1934-9556-60.6.484
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations Among Children and Youth With Autism in the United States: Frequency, Characteristics, and Costs

Abstract: National estimates of hospitalization diagnoses and costs were determined using the 2016 HCUP Kids' Inpatient Database. Children and youth with autism were hospitalized over 45,000 times at over $560 million in costs and 260,000 inpatient days. The most frequent principal diagnoses for hospitalizations of children and youth with autism were epilepsy, mental health conditions, pneumonia, asthma, and gastrointestinal disorders, which resulted in almost $200 million in costs and 150,000 inpatient days. Mental hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Ames and coworkers showed that adolescents with autism had more complex needs for psychiatric and health care, which meant they had to pay more money or effort for interventions ( 10 ); children with ASD and gastrointestinal symptoms paid more money or effort for interventions. Children and adolescents with autism have a higher rate of hospitalization for gastrointestinal disorders than the general population ( 11 ). In 2014, McElhanon et al reported that children with ASD have higher prevalence of GI symptoms than TD children, through a study investigating gastrointestinal symptoms in In children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Ames and coworkers showed that adolescents with autism had more complex needs for psychiatric and health care, which meant they had to pay more money or effort for interventions ( 10 ); children with ASD and gastrointestinal symptoms paid more money or effort for interventions. Children and adolescents with autism have a higher rate of hospitalization for gastrointestinal disorders than the general population ( 11 ). In 2014, McElhanon et al reported that children with ASD have higher prevalence of GI symptoms than TD children, through a study investigating gastrointestinal symptoms in In children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have examined hospitalizations among autistic youth, there is minimal research that provides a systematic picture of nationwide, all-payer, mental health–related hospitalizations in community-based hospitals. The existing literature suggests that autistic youth are more commonly hospitalized for psychiatric conditions than allistic youth or youth with chronic conditions (Carbone et al, 2015; Croen et al, 2006; McMaughan, Imanpour et al, 2022; Nayfack et al, 2014). Moreover, having a mental health condition is a risk factor for hospitalization for autistic youth (Righi et al, 2018) and the risk of psychiatric hospitalization increases with age (Mandell, 2008).…”
mentioning
confidence: 99%